2011
DOI: 10.1186/1475-2875-10-99
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behaviour as determinants of anti-malarial drug use in a peri-urban population from malaria holoendemic region of western Kenya

Abstract: BackgroundThe appropriate use of anti-malarial drugs determines therapeutic efficacy and the emergence and spread of drug-resistant malaria. Strategies for improving drug compliance require accurate information about current practices at the consumer level. This is to ascertain that the currently applied new combination therapy to malaria treatment will achieve sustained cure rates and protection against parasite resistance. Therefore, this cross-sectional study was designed to determine knowledge and behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 15 publications
10
31
2
Order By: Relevance
“…Four studies [14,20,27,32] reported on the association between income level and antimalarial drug use behaviours of non-adherence to the treatment dosage [20,27,31] and non-compliance to treatment guideline in the form of self-medication [15,23,30]. All of these studies were conducted in Africa.…”
Section: Income/socioeconomic Level and Antimalarial Drug Use Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies [14,20,27,32] reported on the association between income level and antimalarial drug use behaviours of non-adherence to the treatment dosage [20,27,31] and non-compliance to treatment guideline in the form of self-medication [15,23,30]. All of these studies were conducted in Africa.…”
Section: Income/socioeconomic Level and Antimalarial Drug Use Behaviourmentioning
confidence: 99%
“…Of these, 62.7% used the patent medicine dealers [30] Self-diagnosis was the most common diagnostic method in both rural and urban for adult and child diagnosis [16] Reasons for selfmedication 39.0% said less expensive than consultation; 10% said health institution was far away; 12.5% said neighbour/friend/relative previously took the same drug [23] [15,23] For those who had no prescription, the reasons given were as follows: 39.0% said procedure of acquisition (without prescription) was less costly; 23.0% took same drug for similar symptoms; 10% said health institution was far from their location; 12.5% said neighbour/friend/relative previously took the same drug [15]. Household size significantly influenced the types of anti-malarial drugs used (b=0.092, P=0.049).…”
Section: Expected Outcome Unexpected Outcome Studiesmentioning
confidence: 99%
See 3 more Smart Citations